Front Cover. Issue 2 (5th January 2018) - Hulva, Pavel; Černá Bolfíková, Barbora; Woznicová, Vendula; Jindřichová, Milena; Benešová, Markéta; Mysłajek, Robert W.; Nowak, Sabina; Szewczyk, Maciej; Niedźwiecka, Natalia; Figura, Michał; Hájková, Andrea; Sándor, Atilla D.; et al.
Abstract : The cover image, by Pavel Hulva et al ., is based on the Biodiversity Research Wolves at the crossroad: Fission–fusion range biogeography in the Western Carpathians and Central Europe, DOI:10.1111/ddi.12676 . Photo Credit: Stanislav Harvančík.